PERUBAHAN STRUKTUR DAN PERANAN KELUARGA DALAM PJP II - Sofian Effendi; Sukamdi Sukamdi (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 1994)
The achievement of population policy in the last twe decades, infect, has also brought about problems that should be anticipated. Decrease in fertility rate for instance, along with a tendency to live separately from parents and increasing intention to celibacy in turo will result in change of family structure. This change is from extended to nuclear family or even single headed household. It has been accompanied by changing character of parents-children relationship from socio-psychological into economical relationship. In addition, lower mortality rate which also means longer life expectancywould be another problemconcerning aged care. The different pattern of migration among regions or between urban and rural areas, will effect on variation of problems. That means social policies should be implemented by following the variation.